Enhanced capillary performance of ultrathin nylon mesh wick for flexible thermal management systems. (January 2023) - Tang, Yong; Xi, Xiaoqian; Liang, Fuye; Zhang, Shiwei; Tang, Heng; Wu, Chunxia; Sun, Yalong
Highlights: Silica coatings were enveloped on nylon mesh by the sol-gel method and endowed it with superhydrophilicity. Superhydrophilic nylon mesh wicks (SNMWs) yielded good capillary performances. SNMWs with the maximum volumetric flow rate of 1.19 mm 3 /s were promising wicks for flexible heat pipes. SNMWs maintained good capillary performances even after 10, 000 bending cycles. Abstract: The rapid development of flexible electronic devices brings the demand for flexible thermal management systems. Nylon mesh with excellent flexibility is ideal for flexible thermal management systems, especially acting as wicks in flexible heat pipes (FHPs). In this study, novel superhydrophilic nylon mesh wicks (SNMWs) with enhanced capillary performance are fabricated by the sol-gel method. Silica coating is formed on the surface of nylon mesh and endowed the mesh with superhydrophilicity. Capillary rise tests and cyclic bending reliability tests are conducted to evaluate the capillary performance and bending fatigue resistance of the SNMWs. The results show that the SNMWs yield excellent capillary performance, the maximum equilibrated wicking height of the SNMWs reaches 87.38 mm and the largest wicking coefficient is 5.91 mm/s 0.5 . The average volumetric flow rate proportional to wicking velocity and wetted volume is taken as a comprehensive index to evaluate the feasibility of applying SNMWs in FHPs and the maximum average volumetric flow rate reaches 1.19 mm 3 /s. Simultaneously, the SNMWs maintain good capillary performance even after 10, 000 bending cycles, which means strong bending fatigue resistance. This study provides a high-performance, high-reliability, and cost-effective flexible wick for enhancing the thermal performance of FHPs.